2020
DOI: 10.1038/s41598-019-57371-1
|View full text |Cite
|
Sign up to set email alerts
|

20% of US electricity from wind will have limited impacts on system efficiency and regional climate

Abstract: Impacts from current and future wind turbine (WT) deployments necessary to achieve 20% electricity from wind are analyzed using high resolution numerical simulations over the eastern USA. Theoretical scenarios for future deployments are based on repowering (i.e. replacing with higher capacity WTs) thus avoiding competition for land. Simulations for the contemporary climate and current WT deployments exhibit good agreement with observed electricity generation efficiency (gross capacity factors (CF) from simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…The move to reduce energy-related greenhouse gas emissions is gathering international momentum fueled by both the urgent need to reduce anthropogenic forcing of climate [1][2][3] and rapid declines in the cost of renewable generation sources. 4 The government of the United Kingdom has committed to net zero greenhouse gas emissions by 2030.…”
Section: Introductionmentioning
confidence: 99%
“…The move to reduce energy-related greenhouse gas emissions is gathering international momentum fueled by both the urgent need to reduce anthropogenic forcing of climate [1][2][3] and rapid declines in the cost of renewable generation sources. 4 The government of the United Kingdom has committed to net zero greenhouse gas emissions by 2030.…”
Section: Introductionmentioning
confidence: 99%
“…Xia et al (2019) found that the vertical divergence of heat flux and resolved‐scale 3D temperature advection are two important physical processes that could explain the simulated wind farm impacts on temperature. Finally, using a CPRCM projection where 20% of U.S. electricity is produced from wind, climate impacts of wind farms were judged modest compared to that induced by historical changes in land cover and to the global temperature perturbation induced by producing an equivalent amount of electricity with coal (Pryor, Barthelmie, & Shepherd, 2020).…”
Section: Cprcm Benefits For Impact Studiesmentioning
confidence: 99%
“…In all of our experiments, we add wind scenarios until the change in metrics is small, randomly selecting 200 scenarios from the 1,000 wind scenarios available for each season. For higher wind penetration, wind production levels for each site are scaled up equally, reflecting the assumption that existing wind locations are productive sites that could be scaled with larger turbines or site expansion [44].…”
Section: Experiments Setupmentioning
confidence: 99%